2017
DOI: 10.1007/s00586-017-5034-6
|View full text |Cite
|
Sign up to set email alerts
|

Rate of complications due to neuromuscular scoliosis spine surgery in a 30-years consecutive series

Abstract: The surgical treatment in neuromuscular scoliosis is burdened by a large number of complications. An accurate knowledge of possible complications is mandatory to prepare strategies due to prevent adverse events. A difference in definitions could completely change results in good or bad as well as in our same series the adverse events amounted at almost 30% of cases, but complications that due to complete failure would amount at 9.19% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 60 publications
0
11
0
1
Order By: Relevance
“…Several large series of patients with NMS and rates of complications have been published recently. Rumalla et al [34] reviewed 2154 NMS fusion cases from 2002 to 2011 from a national inpatient database, and reported an overall complication rate of 40.1%.Turturro et al [35] reviewed a single center consecutive series of 185 NMS patients over a 30-year time period. These authors reported a rate of adverse events that approached 30%, but specified that the rate of complications that affected the final care of the patient was approximately 9%.…”
Section: Complicationsmentioning
confidence: 99%
“…Several large series of patients with NMS and rates of complications have been published recently. Rumalla et al [34] reviewed 2154 NMS fusion cases from 2002 to 2011 from a national inpatient database, and reported an overall complication rate of 40.1%.Turturro et al [35] reviewed a single center consecutive series of 185 NMS patients over a 30-year time period. These authors reported a rate of adverse events that approached 30%, but specified that the rate of complications that affected the final care of the patient was approximately 9%.…”
Section: Complicationsmentioning
confidence: 99%
“…Rumalla et al reviewed 2154 spinal surgeries, which were performed for patients with neuromuscular scoliosis, and reported an overall complication rate of 40.1% [10]. Turturro et al reviewed the outcome of surgery in a consecutive series of 185 patients with neuromuscular scoliosis over 30 years and reported a 30% rate of adverse events [11]. Considering the high rate of complications following the surgical treatment of neuromuscular spinal deformities, brace-wearing treatment contains a critical value in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…One of these classifications divides complications into intraoperative and early and late postoperative. 11 Respiratory disorders are the most frequent postoperative complications in most studies and most observed in individuals with forced vital capacity below 50% in the preoperative period. In these cases, noninvasive ventilation before surgery can decrease postoperative risks, especially when vital capacity is below 40% of predicted values.…”
Section: Postoperative Complications In Neuromuscular Scoliosismentioning
confidence: 99%